Pregnancy following Radical Resection of Solid Pseudopapillary Tumor of the Pancreas - James M. O'Brien; Debra Gussman; Ellen Hagopian; Theodore Matulewicz (Hindawi Limited, 2014)
Solid pseudopapillary tumor of the pancreas is a rare tumor seen in predominately young women and carries a low malignant potential. We discuss a patient, who presented to our high risk clinic, with a clinical history of solid pseudopapillary tumor of the pancreas, predating her pregnancy. The patient had undergone previous surgery and imaging which had excluded recurrence of disease; however, increased attention was paid to the patient during her pregnancy secondary to elevated hormonal levels of progesterone, which any residual disease would have a heightened sensitivity to. In cases of pregnant patients with a history of pancreatic tumors, a multidisciplinary approach with maternal fetal medicine, medicine, and general surgery is appropriate and can result in a healthy mother and healthy term infant.